E2F1 activates breast stromal fibroblasts and promotes their paracrine pro-carcinogenic effects - Layla A. Al-Kharashi; Falah H. Al-Mohanna; Abdelilah Aboussekhra; Abdelilah Abousekhra (Scientific Reports)
Abstract Breast cancers (BC) are complex neo-organs composed of neoplastic as well as non-carcinogenic cells, in addition to a dynamic extracellular matrix. Active cancer-associated fibroblasts (CAFs) play major roles in the development and spread of breast cancers, through paracrine signaling, which are under the control of several transcription regulators. In the present study, we investigated the role of the transcription factor E2F1 in the active status of CAFs. We have shown that CAFs express higher levels of E2F1 compared to their adjacent tumor counterpart fibroblasts (TCFs). Importantly, E2F1 upregulation by ectopic expression transactivated quiescent breast stromal fibroblasts and promoted their paracrine pro-carcinogenic effects. Indeed, E2F1-expressing fibroblasts were more efficient than their corresponding controls in enhancing the epithelial-to-mesenchymal transition and stemness processes in breast cancer cells both in vitro and in vivo. However, E2F1 knock-down normalized breast CAFs and suppressed their paracrine pro-carcinogenic effects. Interestingly, while fibroblasts expressing high level of E2F1 enhanced the resistance of BC cells to chemotherapeutic drugs, E2F1-deficient fibroblasts enhanced their sensitivity to cisplatin. Together, these findings indicate that the transciption factor E2F1 plays a critical role in the transactivation of breast stromal fibroblasts, and therefore could be a great therapeutic target for precision therapeutics of BC patients.